Using communicative activities to increase students’ production in english grammar classes at Francisco de Orellana high school - Vera Morales, Cindy Nathaly (2015)
The main purpose of this Research Project is to increase students’ grammar production through the use of communicative activities in students of ninth grade at Francisco de Orellana High School. For achieving this goal, the objectives set where to find out the reasons why students have a low level of grammar production, and to elaborate a set of communicative activities. As part of this process, class observations and surveys to students and teachers were applied inside the classroom to know difficulties they were facing. Later on, after analyzing and comparing the data obtained through the instruments, it was displayed the factors that were affecting the development of communicative competences, most of them had to deal with teachers’ aspects…..